Sweet Potato Leaf Extract as a Protective Antioxidant: Improving Hematological Health in Ammonia-Exposed Mahseer Fish - Anggreani, Shovia Finny; Imlani, Ainulyakin Hasan; Kenconojati, Hapsari; Budi, Darmawan Setia; Suciyono, Suciyono (Universitas Airlangga, 2025)
The Mahseer fish (Neolissochilus soroides) is a highly valuable aquaculture species due to its economic potential. Currently, this species is being developed in intensive aquaculture systems. As a result, ammonia levels are increasing, which could potentially disrupt the growth and survival of the fish. This study aimed to investigate the effects of sweet potato (Ipomoea batatas) leaf extract supplementation as an antioxidant on the hematological profile of Mahseer fish exposed to NH4Cl. Four supplementation treatments were employed: 0%, 2.5%, 5%, and 7.5%, each with five replicates. The fish were supplemented with the extract for 40 days and exposed 10 ppm NH4Cl for 48 hours. Blood samples were collRected before rearing, after 40 days of supplementation and NH4Cl exposure. The results demonstrated that supplementation with sweet potato leaf extract (SPLE) positively influenced the hematological profile of mahseer. Specifically, higher doses of the extract enhanced immunity across all treatments. Notably, only the highest doses of 7.5% and 5% effectively mitigated fish stress induced by ammonia exposure for 24 hours. Furthermore, there were no significant differences observed among treatments in response to NH4Cl exposure throughout the study period. These findings underscore the potential of SPLE as an antioxidant supplement to bolster immune function and alleviate oxidative stress in mahseer under ammonia exposure conditions. Further research could focus on optimizing the dosage of SPLE to maximize its antioxidant benefits in aquaculture setting.